Lumberjanes (2014), issue 12 ebook - Watters, Shannon (Lumberjanes (2014)., 2015)
Mal and Molly just want to get back to their friends, but things are looking more dire by the minute. It's going to be a crazy dash through this weird mixed-up world as they try to not only find a working portal, but one that will take them back to camp!